Pastors' Perceptions of the Black Church's Role in Teen Pregnancy Prevention. Issue 3 (May 2020) - Wright, LaNita S.; Maness, Sarah; Branscum, Paul; Larson, Daniel; Taylor, E. Laurette; Mayeux, Lara; Cheney, Marshall K.
Objective . To identify pastors' perceptions of the Black Church's role in promoting adolescent sexual health and preventing teen pregnancy. The Black Church and pastor are important partners in addressing health disparities in the Black community, especially those addressing sensitive issues as teen pregnancy. Methods . Semistructured interviews ( n = 31) were conducted with Black Church pastors in two southwestern U.S. cities from September 2014 to July 2015. The question path was developed based on interviews with local leaders, literature searches, and key informant pastor interviews. Questions included knowledge/beliefs about sexuality education, church's role in preventing teen pregnancy, and implementation obstacles. Interviews were transcribed and thematically analyzed. Results . (1) All pastors believed that the Black Church should address teen pregnancy with parents and congregants. (2) Two major obstacles emerged: (a) all pastors perceived social consequences, including resistant parents and (b) discomfort discussing contraceptives/condoms. (3) All pastors were willing to partner with organizations, but most had reservations based on conflicting missions/values. Conclusions . Black Church pastors support teen pregnancy prevention programs in the church; however, public health partners must be willing to address the church's unique needs and mission.